Generation of the Human iPSC Line from Spontaneous Late-Onset Alzheimer's Disease Patient with ApoE3/3 Genotype and Sex-, Age-, and ApoE-Matched Healthy Control - Kadakova, Sona; Raska, Jan; Hribkova, Hana; Fedorova, Veronika; Sedmik, Jiri; Plesingrova, Klara; Sheardova, Katerina; Bohaciakova, Dasa (Stem cell research, 2024)
Human induced pluripotent stem cell (iPSC) lines were generated from peripheral blood mononuclear cells (PBMCs) isolated from a patient diagnosed with spontaneous late-onset Alzheimer's disease (AD) carrying ApoE3/3 gene and one age-, sex-, and ApoE-matched healthy control. Reprogramming was done using a commercially available Epi5 Reprogramming Kit containing OCT4, SOX2, KLF4, LIN28, and L-MYC as reprogramming factors. The pluripotency of the iPSC lines was verified by the expression of pluripotency markers and by their capacity to differentiate into all three embryonic germ layers in vitro. These newly established iPSC lines offer a valuable platform for in vitro modeling of AD.
Keywords: Krüppel-like faktor 4; Alzheimerova nemoc; Cell Differentiation; Leukocytes, Mononuclear; lidé; buněčná diferenciace; Apolipoprotein E3; Genotype; indukované pluripotentní kmenové buňky; apolipoprotein E3; genotyp; Induced Pluripotent Stem Cells; Alzheimer Disease; Kruppel-Like Factor 4; leukocyty mononukleární; Humans